2018
DOI: 10.1016/j.chom.2018.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Formation of the Microbial and Immunological Environment of the Human Airways

Abstract: Crosstalk between immune cells and the microbiota in mucosal tissues can set an individual on a trajectory toward health or disease. Little is known about these early-life events in the human respiratory tract. We examined bacterial colonization and immune system maturation in the lower airways over the first year of life. The lower respiratory tract microbiota forms within the first 2 postnatal months. Within the first weeks, three microbial profiles are evident, broadly distinguished as dysbiotic or diverse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 49 publications
5
88
0
1
Order By: Relevance
“…Similar to our results where an association in a co-occurrence network of Fusobacterium and Prevotella was observed such an interaction was also described for the lung microbiome of healthy individuals [4]. Cluster 6 included the genera Neisseria and Streptococcus , both have recently been proposed as keystone species for the community structure of healthy neonatal airways [50].…”
Section: Resultssupporting
confidence: 87%
“…Similar to our results where an association in a co-occurrence network of Fusobacterium and Prevotella was observed such an interaction was also described for the lung microbiome of healthy individuals [4]. Cluster 6 included the genera Neisseria and Streptococcus , both have recently been proposed as keystone species for the community structure of healthy neonatal airways [50].…”
Section: Resultssupporting
confidence: 87%
“…7_1_47FAA (Figure 6D, Table S3). We observed a lower relative abundance of Ureaplasma parvum in individuals who delivered by cesarean section (Figure 6E, Table S3), a bacterium commonly isolated from pregnant women (Anderson et al, 2013) and recently reported in the lower respiratory tract of preterm infants (Pattaroni et al, 2018) and in preterm placenta (de Goffau et al, 2019). Compared with vaginal deliveries, the plasma concentrations of testosterone, androstenedione, methionine, threonine and tryptophan were significantly lower in women who experienced caesarean section (Figure 6D, 6E).…”
Section: Resultssupporting
confidence: 52%
“…48,52,53 Studies by our group have indicated that the airway microbiome forms rapidly post-birth, reaching its mature diversity within 2-3 post-natal weeks in mice 54 and 2-3 post-natal months in humans. 55 In mice, formation of the airway microbiome coincides with immune maturation steps that underlie the development of tolerance to inhaled allergens. 54 In humans, it is not feasible to track the lower airway microbiome longitudinally, however, the constituents of the microbiome associated with distinct steps of immune maturation indicative of ongoing crosstalk between the airway resident microbes and immune cells.…”
Section: The Gut Microbiotamentioning
confidence: 99%